Student’s digital literacy competence and its implications for the learning process - Iskandar Zulkarnain; Yovita Sabarina Sitepu; Raras Sutatminingsih; Mickhael Rajagukguk (Institute of Advanced Engineering and Science, 2024)
This study measures and compares the digital literacy index between general and vocational high school students. The aim is to determine each student’s ability to understand and implement literacy skills in the digital space. The notes from the findings of this study are then related to the proper implementation of the learning process between the two groups of education levels. This study uses quantitative methods, with the research design as a survey. The population of this research is general and vocational high school students in Medan, Indonesia using a margin of error of 5%. The sampling technique in this study used the quota sampling method proportionally to 400 respondents, with 220 respondents coming from general high school education level and 180 respondents from vocational education level. The results of this study indicate that vocational high school students have a higher digital literacy index than general high school students.